Pengaruh pengetahuan tentang riba terhadap minat menabung di Bank Syariah pada kalangan mahasiswa FEBI Universitas Islam Negeri Sumatera Utara - Cahaya, Lin Arshy; Nurlaila, Nurlaila (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Financial institutions emerged in the economy following the use of money as a medium of exchange, initially serving as a vessel and also a liaison between people who needed money for a specific purpose and people who had excess money. This study aims to examine the effect of interest in saving in Islamic banks, especially among FEBI students at UIN North Sumatra. The research method used is quantitative. The data collection instrument uses a questionnaire, which is also used as primary data, and then the results of the data obtained are analyzed with several tests, namely validity tests, reliability tests, simple linear regression by carrying out normality tests, determination tests (R square), and partial tests (t) with a sig level of 5% ( = 0.05), which is assisted in processing by SPSS version 25. The results of this study indicate that there is an effect of knowledge about usury on the intention to save in Islamic banks among FEBI students at UIN North Sumatra. The results of the t test show that knowledge about usury has an effect and sig. of 0.000.